Training of Banana Dodol Production at Ladang Bambu Village, Medan Tuntungan - sigalingging, Riswanti (Talenta Publisher Universitas Sumatera Utara, 2022)
Bananas are generally susceptible to mechanical, physiological, chemical and microbiological damage if handled inappropriately, thus requiring diversification in processing. Various ways of processing bananas have been developed to make various products with varied flavours, such as banana dodol. This service aims to provide knowledge about correctly processing banana dodol to produce delicious banana dodol with an attractive appearance, extend shelf life, increase the economic value of agricultural products, and increase food diversity. Providing technical guidance related to making banana dodol into food products can open new businesses for the community in district V of Ladang Bambu, Medan Tuntungan. Barangan bananas are preferable to using Kepok bananas in making banana dodol.